Come homicide or high water - Swanson, Denise (Swanson, Denise. Welcome back to Scumble River., 2020)
"School psychologist Skye Denison-Boyd is getting ready to return to work from her maternity leave and hoping for a peaceful year in her job as a school psychologist. But when an elderly woman disappears on her first day back and a disgruntled parent threatens to sue the school, Skye realizes that her return will be anything but quiet. When the parent suing Skye's school is found dead and with the missing woman's case is still unsolved, Skye suspects the crimes are somehow linked. With her chief of police husband, Wally, at her side, Skye dives into the investigations. But as tensions rise and Skye and Wally's suspect list lengthens, they start to wonder whether a member of their own tight-knit community could be behind it all..."--Page 4 of cover